ANALISIS TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN MIE MUSBAR TERHADAP ATRIBUT PRODUK - Tito Kartika Candra; Cepriadi '; Jum’atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Mie Musbar an agroindustrial enterprises households the first introduced in Pekanbaru wet noodle products since 1962. This study conducted in June 2014 through the month of August 2014. The method used survey with purposive sampling and non-probability sampling by sample selection was based on the meaning that the sampling is not random with consideration of consumers buying more than 2 times, and satisfaction analysis method using Importance and Performance Analysis (IPA), Customer Satisfaction Index (CSI) and loyality analysis using Switcher Buyer, Habitual Buyer, Satisfied Buyer, Liking The Brand, and Committed Buyer. The results of satisfaction analysis (IPA), Costumer Satisfaction Index (CSI), and loyality analysis, it can be concluded that consumers Mie Musbar “satisfied” and “loyal” to the product attributes of Mie Musbar. Key Word: Satisfaction, Loyality, Product Attributes